Enhancement of pupil-masked wavelength-scale gas-filled flat acoustic lens based on anomaly apodization effect; Physics Letters A; Vol. 383, iss. 5 - Rubio C. Constanza; Tarrazo-Serrano D. Daniel; Minin O. V. Oleg Vladilenovich; Uris A. Antonio; Minin I. V. Igor Vladilenovich (2019, 2019)
Title screen